Prognostic value of the high-sensitivity troponin T assay after percutaneous intervention of chronic total occlusions. Issue 7 (July 2018) - Cottens, Daan; Maeremans, Joren; McCutcheon, Keir; Lamers, Scott; Roux, Lien; Duponselle, Jolien; Bennett, Johan; Dens, Jo
Abstract : Aims: The prognostic value of postprocedural high-sensitivity troponin T (hs-TnT) after percutaneous coronary intervention (PCI) of chronic total occlusions (CTO) is currently unclear. We aimed to assess the prognostic value of elevated hs-TnT after elective CTO-PCI. Methods: The current study included 409 patients undergoing elective CTO-PCI between September 2011 and August 2016 at two centres who had postprocedural hs-TnT measurements available. Clinical, angiographic and procedural characteristics were correlated with any or at least five times the 99th percentile hs-TnT elevation, as well as a 1-year combined endpoint of major adverse cardiac and cerebrovascular events (MACCE) and mortality. Results: Post-CTO-PCI hs-TnT elevation was observed in 85% ( n = 349/409) and at least five times hs-TnT elevation occurred in 42% ( n = 172/409) of cases. hs-TnT elevation was more frequent in more complex patients (postcoronary artery bypass grafting, peripheral vascular disease, chronic kidney disease, heart failure and multivessel disease) as well as in the more complex CTO procedures (higher Japanese CTO complexity, use of retrograde and antegrade dissection re-entry techniques). After 1 year of follow-up (FU), MACCE was not associated with postprocedural hs-TnT elevation, both any elevation (10.9 vs. 11.7%; P = 0.846) and at least five times hs-TnT elevation (15.7 vs. 11.7%; P = 0.451; hazard ratio = 1.375, confidence interval: 0.599–3.157, P = 0.453), compared with no elevation. A nonsignificant trend towards higher mortality in the at least five times hs-TnT vs. no elevation group (4.7 vs. 0%; P = 0.091) was observed. Conclusion: In patients undergoing CTO-PCI, postprocedural hs-TnT elevation is frequent, but is not correlated with higher MACCE and mortality rates after 1-year FU in our small study population, suggestive of the limited long-term impact of troponin elevation.